The Role of Birth Certificates in the Population Administration System for Children in Indonesia - Hafidati, Putri (IJBLE Scientific Publications Community Inc., 2025)
Parents must record the birth of their child, as it is a legal requirement for citizens to have their births registered. By the applicable Law, this recording is carried out through a specific procedure and archived in a sheet that is then known as the